L'Afrique en prisons - Le Marcis, Frédéric; Morelle, Marie (Sociétés, Espaces, Temps, 2022)
Since Florence Bernault's book on the history of African prisons, the French-speaking social sciences have remained singularly silent on the issues of prison in Africa. The aim of this book is to fill that gap, working from ethnographic research (interviews, field surveys, consultation of archives) conducted by a multidisciplinary team in ten countries around French- and English-speaking Africa: Senegal, Burkina Faso, Ivory Coast, Ghana, Nigeria, Cameroon, Tunisia, Ethiopia, Burundi, and South Africa. Breaking with the archetypal and incomplete images often conveyed about the continent's prisons, this book offers a nuanced reading of the prison experience formulated in terms of representations of justice. By presenting the prison phenomenon in a historical context, it opens the issue of prison reform up to analysis. Lastly, this work invites us to consider how prison impacts the world beyond its walls. This book will be of interest not only to researchers and students, but also to the many actors involved in prison work and in debates about prison reforms and the purpose of prison.